1986
DOI: 10.1002/1520-6297(198621)2:1<33::aid-agr2720020104>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Foreign market promotion programs: An analysis of promotion response for apples, poultry, and tobacco

Abstract: US exports of apples, poultry, and unmanufactured tobacco were analyzed using regression techniques to determine their responsiveness to foreign market development expenditures. It was determined that apple and tobacco exports were responsive, while poultry exports were not. Marginal returns to an additional dollar of export promotion for apples and tobacco were $60 and 31, respectively. Results indicated that response to poultry promotion was not different from zero. This is likely due to aggregation of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A considerable number of studies have examined export demand and the impacts of U.S. export promotion programs on various agricultural commodities in importing countries. For example, studies have encompassed measuring the effectiveness of U.S. export promotion programs for meat and poultry products (Comeau, Mittlehammer, & Wahl, 1997;Le, Kaiser, & Tomek, 1997), fruit and fruit products (Armah & Epperson, 1997;Fuller, Bello, & Capps, 1992;Rosson, Hammig, & Jones, 1986), tree nuts (Halliburton & Henneberry, 1995;Kinnucan & Christian, 1997;Weiss, Green, & Havenner, 1996), and tobacco (Rosson et al, 1986).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable number of studies have examined export demand and the impacts of U.S. export promotion programs on various agricultural commodities in importing countries. For example, studies have encompassed measuring the effectiveness of U.S. export promotion programs for meat and poultry products (Comeau, Mittlehammer, & Wahl, 1997;Le, Kaiser, & Tomek, 1997), fruit and fruit products (Armah & Epperson, 1997;Fuller, Bello, & Capps, 1992;Rosson, Hammig, & Jones, 1986), tree nuts (Halliburton & Henneberry, 1995;Kinnucan & Christian, 1997;Weiss, Green, & Havenner, 1996), and tobacco (Rosson et al, 1986).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of research conducted by Rosson et al (1986) indicated that promotion activities boosted export sales of apples and tobacco. They found that export revenues of $60 and $31 were generated for U.S. apples and tobacco, respectively, per dollar of promotion expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosson et al (1986) evaluated export promotion of US apples, poultry, and unmanufactured tobacco. For every dollar endowed in export promotion, marginal returns for apples and tobacco increased $60 and $31, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One way to promote agricultural exports in foreign markets is by pursuing nonprice promotion programs. Several studies (e.g., Williams, 1985;Rosson, Hammig, and Jones, 1986) have shown that returns per dollar invested in promotional activities are quite high compared to the returns from a price subsidy program such as the EEP (Seitzinger and Paarlberg, 1990). Solomon and Kinnucan (1993), in an analysis of the effects of nonprice export promotion on cotton, found promotional programs have a carryover period lasting beyond one year.…”
mentioning
confidence: 99%